Post anaesthesia cognitive outcomes in propofol vs. ketamine sedation for colonoscopy: a retrospective cohort study - Zook, Zachary R.; Chien, Stephen; Deng, Ashley; Espiridion, Eduardo (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2025)
Purpose Colorectal cancer is the third most common malignancy worldwide and the second leading cause of cancer-related mortality. Colonoscopy, the primary screening method for this disease, typically involves sedation to enhance patient comfort and ensure a thorough examination. The choice of sedative is particularly important for older adults, as sedation can have implications on cognitive function. This study aims to evaluate the long-term cognitive effects of propofol and ketamine by examining the risk of developing dementia, disorientation, and depression following colonoscopy. Methods Utilizing data from the TriNetX platform, we compared two cohorts of patients who had undergone a colonoscopy and received either exclusively propofol ( n = 1,938) or ketamine ( n = 1,938) for sedation. Measures of association and survival were analyzed using TriNetX. Odds ratios (OR) were calculated from logistic regression to compare the cohorts. Survival analysis was conducted using the Cox proportional hazards model to find hazard ratio (HR). Results One of the most notable findings was the association between ketamine use and an increased risk of disorientation, with an odds ratio of 0.489 and a hazard ratio of 0.443 for propofol compared to ketamine. Regarding dementia, the lower OR (0.603) and HR (0.561) associated with propofol suggest that it may have a comparatively safer profile concerning long-term memory and cognitive decline. The findings also demonstrated a significant difference in depression rates, with propofol showing reduced odds (0.740) and risk ratios (0.688) of postprocedural depression compared to ketamine. Conclusion These findings suggest that propofol may offer a safer cognitive profile than ketamine, particularly for older patients and those at risk of cognitive decline. Given the increasing number of older adults undergoing colonoscopy, these results highlight the importance of selecting sedative agents that balance immediate procedural needs with long-term cognitive health.